2007
DOI: 10.1016/j.juro.2006.10.095
|View full text |Cite
|
Sign up to set email alerts
|

Phalloplasty and Urethroplasty in Children With Penile Agenesis: Preliminary Report

Abstract: Opposite gender should not be assigned in patients affected by penile agenesis, who are better raised according to their karyotype and hormonal production. Definitive phalloplasty in adults may achieve good results. Nevertheless, this procedure is generally performed in postpubertal boys and it is not easily available everywhere. Therefore, we believe that social and psychological concerns justified this type of phalloplasty as a palliative preliminary procedure in 3 of our patients. In those countries where d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0
7

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 17 publications
0
33
0
7
Order By: Relevance
“…Studies to evaluate the long-term results have shown viability of neophallus bone resulting in a satisfactory cosmetic and functional outcome [25]. The longterm complications of early phalloplasty using abdominal wall skin flap include dorsal urethral dehiscence resulting in an epispadiac urethra and necrosis of the distal urethra [21]. One of our cases (case 2) had a stenotic urethral opening and died because of urosepsis.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Studies to evaluate the long-term results have shown viability of neophallus bone resulting in a satisfactory cosmetic and functional outcome [25]. The longterm complications of early phalloplasty using abdominal wall skin flap include dorsal urethral dehiscence resulting in an epispadiac urethra and necrosis of the distal urethra [21]. One of our cases (case 2) had a stenotic urethral opening and died because of urosepsis.…”
Section: Discussionmentioning
confidence: 76%
“…In 2007, an article by De Castro et al [21] influenced change the management of aphallia. They proposed that the opposite sex should not be assigned in patients affected by aphallia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…He stated that the long-term sexual function of his patients would be reported later on; at the time of publication of his study, none of his patients were sexually active. De Castro et al [4] in their landmark study mentioned that they performed phalloplasty and urethroplasty in all their patients using the abdominal skin flap. …”
Section: Discussionmentioning
confidence: 99%
“…It can coexist with other congenital defects [1,2] . There is a paucity of papers written in English which describe reconstruction of the urethra in patients suffering from aphallia [3][4][5] . The few articles which do exist are single case reports and contain only a brief description of the surgery undertaken [6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%